132 ft / sec. I believe this is the answer.
Answer:
Yes, it is.
Step-by-step explanation:
The hypothesis made on the Hoxd13 gene expression justified the results obtained. This is because if one of the three segments is removed, the value of the expression level will be reduced to approximately below 100% of the control. Therefore, it can be inferred that the theoretical analysis justified the results obtained.
9514 1404 393
Answer:
a) CP = SP/1.1
b) CP = $59.50
c) GST = $5.95
Step-by-step explanation:
a) Divide by the coefficient of CP.
SP = 1.1×CP
CP = SP/1.1
__
b) Use the formula with the given value.
CP = $65.45/1.1 = $59.50
__
c) You can do this two ways: subtract CP from SP, or multiply CP by 0.1.
GST = SP -CP = $65.45 -59.50 = $5.95
GST = CP×0.10 = $59.50 × 0.10 = $5.95
37 is 26%(rounded up to the nearest percent) of 144
Answer:
(x - 8)(2x + 3)
Step-by-step explanation:
To factor a polynomial of the form
ax² + bx + c,
follow these steps:
1) Multiply ac together.
2) Find 2 factors of ac that add to b. Call these factors p and q.
3) Break up the middle term of the polynomial into px + qx.
4) Factor by grouping.
Now let's follow the steps above with your problem.
You are given the polynomial
2x² - 13x - 24,
so a = 2, b = -13, and c = -24
1) Find ac.ac is the product 2(-24) = -48
2) Now we need to find 2 factors of -48 that add to b, -13.
I know that 48 = 3 × 16, so if we use -16 and 3 for the two numbers, we have
-16 + 3 = -13
and -16 × 3 = -48.
3) Now we break up the middle term of the polynomial, -13x, into -16x + 3x.
The polynomial is now
2x² - 16x + 3x - 24
4) We factor the polynomial by grouping. To factor by grouping, you factor a common factor out of the first 2 terms and factor out a common factor out of the last two terms.
2x² - 16x + 3x - 24 =
= 2x(x - 8) + 3(x - 8)
We now see the common factor of x - 8, so we factor that out.
= (x - 8)(2x + 3)
Answer: (x - 8)(2x + 3)